"Perfectly supportive in theory…": Women's perceptions of partner support while breastfeeding. (September 2022) - Johnson, Katherine M.; Slauson-Blevins, Kathleen S.
Breastfeeding is an important public health issue that significantly intersects with work, gender, and family relationships. Prior research has focused on partner dynamics in the breastfeeding family and specifically shown that male partners heavily influence women's breastfeeding decisions and experiences. Much of this research emphasizes net gains of men's involvement in breastfeeding. While acknowledging the importance of involved fathers early on, we argue for recognizing the dual potential for men's involvement in breastfeeding to be both affirming and undermining to their breastfeeding partners. As part of a workplace case study, we conducted semi-structured, in-depth interviews with 32 women who were currently or recently breastfeeding. We identified four major themes: (1) encouraging/discouraging breastfeeding, (2) acknowledging/overlooking breastfeeding labor, (3) supporting/undermining breastfeeding decisions and goals, and (4) assisting with/avoiding domestic labor. Education directed at men should address the issue that not all intended support actions may be perceived as supportive by breastfeeding women and should provide concrete guidance on how men can be supportive, centering the needs of breastfeeding women.